2002
DOI: 10.1038/sj.bjc.6600119
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hyperfractionation (AHF) compared to conventional fractionation (CF) in the postoperative radiotherapy of locally advanced head and neck cancer: influence of proliferation

Abstract: Based on the assumption that an accelerated proliferation process prevails in tumour cell residues after surgery, the possibility that treatment acceleration would offer a therapeutic advantage in postoperative radiotherapy of locally advanced head and neck cancer was investigated. The value of T pot in predicting the treatment outcome and in selecting patients for accelerated fractionation was tested. Seventy patients with (T2/N1 -N2) or (T3-4/any N) squamous cell carcinoma of the oral cavity, larynx and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 25 publications
(31 reference statements)
1
59
0
3
Order By: Relevance
“…It indicates accelerated repopulation of cells surviving the induction chemotherapy course. Our findings are in line with those of others who observed a rapid regrowth after irradiation of pulmonary metastases (Battermann et al, 1981), and after surgery in head-and-neck cancer (Trotti et al, 1998;Ang et al, 2001;Awwad et al, 2002). In their review, Davis and Tannock Accelerated regrowth of NSCL tumours after chemotherapy SY El Sharouni et al (2000) reported on repopulation of tumour cells between cycles of chemotherapy as a neglected factor.…”
Section: Repopulation and Tumour Doubling Timesupporting
confidence: 91%
“…It indicates accelerated repopulation of cells surviving the induction chemotherapy course. Our findings are in line with those of others who observed a rapid regrowth after irradiation of pulmonary metastases (Battermann et al, 1981), and after surgery in head-and-neck cancer (Trotti et al, 1998;Ang et al, 2001;Awwad et al, 2002). In their review, Davis and Tannock Accelerated regrowth of NSCL tumours after chemotherapy SY El Sharouni et al (2000) reported on repopulation of tumour cells between cycles of chemotherapy as a neglected factor.…”
Section: Repopulation and Tumour Doubling Timesupporting
confidence: 91%
“…This is a matter of intense exploration in recent head and neck cancer clinical trials. 14,15 In our present study, 2 types of fractionation regimens were selected to explore the predictive potential of biological markers studied. The relative response of cells to fractionated regimens depends on the ␣/␤ values of the irradiated tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches have been shown to result in a modest gain in curing head and neck cancer when tested in randomized trials (Garden, 2001). Also, combinations of hyperfractionated and accelerated schedules have been shown to be especially successful for rapidly dividing tumors (Awwad et al 2002). The disadvantage of these new treatment techniques is the higher rates of acute toxicity, especially mucositis.…”
Section: Radiotherapymentioning
confidence: 99%
“…Such interruptions must be prevented, because they may result in prolongation of treatment time and thus a reduction in therapeutic effect (Fowler, 1986). As mentioned before, hyperfractionation, accelerated fractionation, and radiochemotherapy, although especially successful for the treatment of rapidly dividing tumors, result in higher rates of acute toxicity, especially mucositis (Bensadoun et al, 2001;Awwad et al, 2002).…”
Section: Oral Mucosamentioning
confidence: 99%